Acute exposure of perchlorate on zebrafish larvae: Neurotoxicity during development - Xiaoran Xue; Zaiqiu Zhang; Yang Yang; Lin Hu; Mingyi Zhao; Qingnan He (Ecotoxicology and Environmental Safety)
Objective: This study aimed to assess the acute developmental toxicity of perchlorate exposure and identify its manifestation of neurotoxicity in zebrafish (Danio rerio) model. Methods: Zebrafish larvae were exposed to sodium perchlorate at early developmental stages and the phenotypes of various developmental abnormalities were observed and recorded. Neurodevelopmental toxicity has been studied in particular in terms of central nervous system apoptosis, peripheral motor abnormalities, and abnormal autonomic motor behavior. Samples were processed for pathological, transcriptomic, and PCR analyses. Results: Acute exposure of zebrafish larvae to perchlorate resulted in developmental toxicity in a concentration-dependent manner. Heart rate abnormality (33 %), slow blood flow (37 %), abnormal size of liver (23 %), delayed yolk absorption (70 %), and abnormal body pigmentation (100 %) were observed in the 3.83 mg/mL group. Heart edema (10 %), heart rate abnormality (60 %), slow blood flow (67 %), abnormal size of liver (77 %), delayed yolk absorption (100 %), abnormalities in intestinal morphology (30 %), abnormal body pigmentation (100 %), and shorter body length (47 %) were observed in the 4.03 mg/mL group. Developmental neurotoxicity was characterized by brain apoptosis, damage to the central nervous system (P < 0.01) and peripheral motor neurons (P < 0.0001), and reduced autonomous motor distance (P < 0.01). Transcriptomic analysis revealed that c3a.1, c5, fga, fgb, and fgg were upregulated in the complement and coagulation cascades, and the mRNA levels of c3a.1, dusp1, slc2a6, purba, and klf9 were found upregulated in PCR. Conclusion: Acute perchlorate exposure on zebrafish larvae caused various developmental toxicity in a concentration-dependent manner, notably neurotoxicity. We believed the immunological and inflammatory responses were involved.